OWN EXPERIENCE OF LASER THERAPY FOR THE PREVENTION AND TREATMENT OF EARLY AND LATE RADIATION-INDUCED SKIN INJURIES IN PATIENTS WITH BREAST CANCER AFTER SIMULTANEOUS RECONSTRUCTIVE PLASTIC SURGERY - S. I. Tkachev; A. V. Nazarenko; E. V. Timoshkina; O. P. Trofimova; V. V. Glebovskaya; S. M. Ivanov; T. N. Borisova (ABV-press, 2017)
Low-energy laser radiation has a good anti-inflammatory and stimulating effect on the damaged tissues; therefore, it can be used for the prevention and treatment of both early and late radiation-induced skin injuries in patients receiving radiotherapy. So far, the effect of low-energy laser radiation in the prevention of radiation-induced skin damage remains poorly understood. This article presents a brief overview of the results obtained in the latest foreign studies as well as own experience of laser therapy for the prevention and treatment of both early and late radiation-induced skin injuries in patients with breast cancer after simultaneous reconstructive plastic surgery.